The Effectiveness of In-Network Methods (Whatsapp Group) to the Attitudes of Covid 19 Prevention of D3 Midwifery Students STIKes Patria Husada Blitar - Ita Noviasari; Levi Tina Sari (STIKes Patria Husada Blitar, 2020)
Covid-19 is a new type of virus that easily spreads to humans and causes serious infections such as pneumonia. In Indonesia, the PSBB (Large-Scale Social Restriction) was implemented as an effort to suppress the spread of the corona virus. All activities outside the home are stopped or reduced until the pandemic has subsided. Some regions have implemented government policies to dismiss their students and begin the application of learning methods using an online or online system. Methods: The design of this study used a quasy experiment with a pre-post group design approach without control group design. A sample of 19 respondents was given material about the definition of covid-19, prevention of covid-19. The sampling technique used purposive sampling. The data collection method used a questionnaire in the form of google form given to respondents before treatment and after treatment. Data analysis was divided into 2, namely univariate and bivariate. Univariate in the form of frequency distribution to measure the characteristics of respondents, namely age, parent's occupation, and bivariate using the Wilcoxon Signed Rank Test statistical test aimed at distinguishing attitudes before and after treatment. Results: The Wilcoxon test proved that there was a difference between before and after treatment, namely Î± (0.05) Ëƒ 0.001. Discussion: Communication with social media via the internet (whatsapps) affected the attitudes of respondents in preventing covid-19 transmission and increase information and understanding for respondents.